Kinetics of halide exchange in cyclopentadienylruthenium bis(triarylphosphine)halides. (1st May 2022) - Bissonnette, Noah B.; Yang, Mulan; Pioch, Thomas; Bussink, Willem; Gaillin, Connor; McCarthy, Eric; Dang, Linh; Kirss, Rein U.
Graphical abstract: Abstract: The kinetics of halide exchange in cyclopentadienylruthenium bis(triarylphosphine) halide complexes CpRu(PAr3 )2 X (1a X = Cl, 1b X = Br, 1c X = I; X′= Cl, Br, Ar = C6 H5, 2 Ar =  p- CH3 OC6 H4, X  = Cl, X′= Br and 3 Ar =  p- FC6 H4, X  = Cl, X′ = Br) have been measured and the results interpreted with respect to two possible mechanisms: halide dissociation vs phosphine dissociation. Halide exchange between n Bu4 NX′ and 1 –3 in fluorobenzene under pseudo-first order conditions is found to be first order in 1 –3. Relative rates of halide exchange follow the order: 1a  > 1b  > 1c > 2 ≈ 3 with activation parameters ΔH † = 117 ± 6 kJ/mol and ΔS † = 44 ± 18 J/mol-K (1a, X′ = Br) and ΔH † = 120 ± 14 kJ/mol ΔS † = 50 ± 45 J/mol-K (1b, X′ = Cl). Plots of kobs vs [X′ – ] for 1 and 2 are consistent with a two-term rate law where kobs = ( k1  +  k2 [X′ – ]) while reactions of 3 are independent of the halide concentration. The rate data are consistent with phosphine dissociation as the rate determining step followed by a slightly faster reaction with halide ions where the dissociated phosphine competes effectively with halide for the open coordination site in a CpRu(PAr3 )X intermediate.